Jenis-Jenis Makrofungi Filum Basidiomycota di Lingkungan Kampus Universitas Mataram - rahman, fatur; Hidayati, Ernin; Ambarawati, Dewi; Sukiman; Sukenti, Kurniasih (Samota Journal of Biological Sciences, 2023)
This research is important to conduct in order to study and explore the macrofungi of the Basidiomycota group in the environment of Mataram University, which can serve as a supporting reference in macrofungi learning and also serve as an initial step in macrofungi conservation. The research is descriptive-exploratory in nature, and the sampling was carried out using the roam method in habitats representing macrofungi of the Basidiomycota division. The results of the study revealed 16 species of macrofungi from the Basidiomycota division, including Schizophyllum commune, Pleurotus ostreatus, Termitomyces sp., Coprinus sp1., Coprinus sp2., Auricularia auricula, Geastrum sp., Pycnoporellus sp., Trametes sp., Trametes sp.2, Ganoderma applanatum, Ganoderma lucidum, Ganoderma sp1., Lentinus tigrinus, Lentinus sp., Picnoporellus sp., and Coprinellus sp. These macrofungi inhabit decaying wood with environmental temperature ranging from 31-32Â°C, air humidity of 77-79%, and soil pH ranging from 5-6, indicating an acidic environment.